2017
DOI: 10.1186/s13037-017-0141-1
|View full text |Cite
|
Sign up to set email alerts
|

Length of stay, costs, and complications in lumbar disc herniation surgery by standard PLIF versus a new dynamic interspinous stabilization technique

Abstract: BackgroundThe number of lumbar spine surgeries has been increasing during the last 20 years, which also leads to an increase in hospital costs and complications related to surgery. Therefore, there is a greater concern about the costs and safety of the techniques and implants used.MethodsPatients (aged from 18 to 50 years) presenting with lumbago /sciatica (ICD-10-CM M54.3, M54.4) due to lumbar disc herniation lasting more than 12 weeks, were included. Patients with disc herniation larger than size-2 or size-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Якщо так, то яким методом? Вибір адекватного методу лікування з великого арсеналу застосовуваних різними авторами методів (пункцій, ендоскопічних, мікрохірургічних, реконструктивних тощо) є однією з найскладніших проблем [6][7][8]. Дані літератури свідчать про те, що автори вирішують цю проблему по-різному, тобто немає єдиного раціонального підходу до її вирішення [9][10][11].…”
Section: Resultsunclassified
“…Якщо так, то яким методом? Вибір адекватного методу лікування з великого арсеналу застосовуваних різними авторами методів (пункцій, ендоскопічних, мікрохірургічних, реконструктивних тощо) є однією з найскладніших проблем [6][7][8]. Дані літератури свідчать про те, що автори вирішують цю проблему по-різному, тобто немає єдиного раціонального підходу до її вирішення [9][10][11].…”
Section: Resultsunclassified
“…Patients undergoing discectomy plus ISP will have a decrease in the mean LOHS when compared to that obtained with discectomy plus PLIF [26].…”
Section: Length Of Hospital Staymentioning
confidence: 90%
“…El-Kadi et al reported patients who underwent UPS and/or BPS by one surgeon at one facility, had positive correlations with LOHS, indicating that those with higher age and BMI would be expected to have a longer length of stay [ 25 ]. Segura-Trepichio et al reported LOHS was significantly lower in the discectomy plus ISP when compared to the PLIF group with microdiscectomy, with an average LOHS of two days versus an average LOHS of five days(P < 0.01) [ 26 ]. Patients undergoing discectomy plus ISP will have a decrease in the mean LOHS when compared to that obtained with discectomy plus PLIF [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Возможны интра-и послеоперационные осложнения после выполнения PlIf/TlIf, такие как повреждение дуральной оболочки, повреждение корешков, псевдоартроз, что также является существенным недостатком ригидной фиксации [43][44][45]. В представленном исследовании частота повреждения дуральной оболочки в группе ДТ составляла 4,6% (n = 5), а в группе Дн ~ 1,0% (n = 1, р = 0,056), что подтверждается данными литературы о риске развития такого осложнения [46,47] и повышения рисков с увеличением сложности проводимого вмешательства [48]. Применение же динамических стержней позволяет минимизировать эти риски и сократить время операции.…”
Section: Discussionunclassified